Economic Value Added of Bangbo Snakeskin Gourami Supply Chain according to the Strategy of Green Agriculture and Environmental Friendliness, Samut Prakan Province - Janvanichyanont, Uraipan; Janwithayanuchit, Isaya; Timmaung, Rattana; Thongkon, Wuthipong; Changtam, Chatchawan; Suntonanantachai, Tanachai (Area Based Development Research Journal, 2019)
The research study aims at developing and strengthening the research management system of Huachiew Chalermprakiet University in order to effectively provide supports for area-based innovative research system and to increase the value of Snakeskin Gourami economic chain. This responds to Samut Prakarn province’s strategic plan to promote agricultural products that are safe and environmentally friendly. After the implementation of research management system, the institution has developed 6 research managers and 80 researchers. Out of 80 researchers, 65 are new with no experience in area-based research. This research has also created an effective change in the system and management mechanism of the university's research both at university level and at faculty level. Regarding the community’s need, 15 innovative research projects were implemented in order to increase the value of Snakeskin Gourami economic chain upstream, midstream and downstream. All research projects are integrated into community services and teaching which provide an opportunity for staff and students to learn and work in the community. At the same time, the community has been developing in various dimensions which are consistent with intended output and outcome. This study also promotes the relationship between the university and networks in the area leading to applicable policy recommendations to meet the needs in the area.